New Technologies for Diagnosis of Periprosthetic Hip Infection - Tarabichi, Majd; Shohat, Noam; Parvizi, Javad (The Journal of Hip Surgery, 2018)
Periprosthetic joint infection (PJI) is a devastating mode of failure following total joint arthroplasty, imposing a serious burden on the healthcare system and society at large. Increasing demand for elective arthroplasty, as well as independent predictions demonstrating future rise in the prevalence of PJI, will lead to an increasing financial burden imposed by this dreadful complication. This challenge is further compounded by disturbing trends, such as drug-resistant organisms among others as a cause of PJI. The aim of this review is to provide the latest updates in the diagnosis of PJI, with a view to identifying areas in need of further research.
Keywords: arthroplasty; periprosthetic joint infection; diagnosis of PJI